A utilização de tecnologias digitais em processos de aprendizagem de instrumentos musicais de cordas friccionadas - Brandão, Elves Souza (2023)
The present work investigates the possibilities of using digital technologies (TDICs) in the learning processes of bowed string instruments. Aspects that permeate Music Teaching in schools are presented; the Teaching of Instruments; and the use of Digital Technologies in Music Education. A brief historical retrospective of music at school is made, showing, in addition to legal documents, the need for the democratization of knowledge, the effective freedom of students in the construction of another educational model and, consequently, another model of school. Researches that relate the teaching of instruments with the use of TDICs have been highlighted in recent decades (GOHN, 2010), however, we consider that the pedagogical-methodological issues have not been properly addressed. This research is specifically based on Learning Bowed String Instruments. To this end, familiarities and skills related to this family of instruments are presented. Still as a theoretical-methodological contribution, we seek to present and explain the main aspects that differentiate the collective teaching of musical instruments (ECIM) from shared musical learning. In chapter two, named METHODOLOGICAL PROCEDURES, the aspects referring to the methodological procedures that are characterized as a qualitative approach were dealt with, since the data were evaluated from the attribution of meanings of the researched subjects. The research field was one of the schools where I work, located in the region of Praia do Futuro, Fortaleza - CE. The public was developed with students from the “Som da Escola” project - basic education students in the Elementary School II stage (6th to 9th grade). For data collection, the following were used: logbook; the application of semi-structured interviews; and observation of the use of applications by students. For data analysis, we used the triangulation technique, as it combines methods and data collection sources (interviews, questionnaires, observation and field notes, among others). In the third chapter, entitled DATA ANALYSIS, an analysis of the research was carried out, where we tried to explain details of the execution phase and the application of the data collection instruments.